MRI An Imaging Tool To Evaluate Cerebral Changes In Victims Of Heat Stroke Presenting With Cerebral Symptoms - Rahila Usman; Nabeel Humayaun Hassan; Saad Ahmed Jilani (Journal of Bahria University Medical and Dental College)
Heat stroke usually presents as medical emergency that causes altered cerebral status and deterioration of multiple organ functions. Heat stroke leads to many different physiological changes within the body, some of which result in neurologic dysfunction. The imaging characteristics of neurological changes of heat stroke are not well documented in literature although the pathophysiologic mechanism of neuronal damage is fairly well understood. We conducted a study to evaluate the imaging appearances of human brain after heat stroke on MRI presented with cerebral symptoms. Material and methods: The retrospective study conducted in radiology department of Ziauddin university hospital from May 2015 till July 2016. All the patients with heat stroke presented with neurological deficit were underwent MRI brain, evaluated by two senior radiologists. Results: 56 patients were included in study, 12 female and 44 male, all patients had clinical symptoms of fever and most of them had additional symptoms of altered level of consciousness. Out of 54 patients, 8 patients had normal MRI brain. 6 patients presented with bilaterally symmetrical hyperintense signals on T2WI in thalami and basal ganglia. 2 patients demonstrated focal high signal intensity in pons representing pontine myelinosis, rest of the patients presented with cerebral or cerebellar infarcts. Conclusion:Many cerebral lesions can result as cerebral damage of heat stroke which includes cerebral infarct, white matter changes, haemorrhages and inflammatory reactions, in these clinical scenarios MRI would be imaging modality of choice to evaluate the disease pattern